(3aGYdjI GdJONd GdeHcQ aj NaV MOI GVWQGH UhQI GdLSe dOi Wad eG bHd GdeOQSI (B/ s - (3aGWeI GdRgQGA eLOi YHOGdSejY eMeOs; (3EjeGf SYjO YHOGdMejO (B: s; (3SgjQ cGed CMeO (B: s ((3GdbGgQI (B: s (3aGWeI GdRgQGA eLOi YHOGdSejY eMeO (B: s, 2016)
(3gOa GdHMK GdMGdi Edi EYOGO HQfGeL ddJONd GdeHcQ bGFe Ydi GdHQeLI GddZhjI GdYUHjI dNaV MOI GVWQGH UhQI GdLSe dOi Wad eG bHd GdeOQSI(B: (3h GdJYQa Ydi aYGdjI gPG GdHQfGeL(B: (3h GdJYQa Ydi GdHQhajd GdSjchdhLi ddGWaGd Phi GVWQGH UhQI GdLSe(B: (3h GdcTa Yf eOi GSJeQGQjI fLGM GdHQfGeL ai NaV MOI GVWQGH UhQI GdLSe dOi Wad eG bHd GdeOQSI(B: (3h bO GSJNOeJ GdHGMKI GdefgL THg GdJLQjHi(B: (3h JchfJ YjfI GdHMK ef (B((310(B) (3CWaGd ef Phi GVWQGH UhQI GdLSe h GdedJMbjf h GdeSJhi GdKGfi ef QjGV GdCWaGd HQhVI eOQSI aVd GdJGHYI dEOGQI GdYeQGfjI(B: (3h GSJNOeJ GdHGMKI ai gPG GdHMK eLehYI ef GdGOhGJ GdSjcheJQjI (B((3GNJjGQ UhQI GdLSe (B- (3SgjQ cGed(B: (3HWQS MGaX(B: (3GNJjGQ GdeUahaGJ Gdedhf (B- (3QGaf(B: (3HQfGeL GdJONd GdeHcQ (B- (3EYOGO GdHGMKI(B): (3h GdGSbGWjI GNJjGQ Jbjje GdehVhY ddGWaGd(B: (3GNJjGQ QSe GdTNU(B: (3GNJjGQ QSe GdCSQI GdeJMQcI(B: (3GNJjGQ QSe GdPGJ eY GdCSQI h eY GdCbQGfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GVWQGH UhQI GdLSe s; (3GdJONd GdeHcQ s; (3GdYdhe GdfaSjI s